Stroke Hospitalizations and Risk Factors - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2012)
Researchers at the Centers for Disease Control and Prevention, Atlanta, GA determined rates of acute stroke hospitalization and the prevalence of stroke risk factors among children and young adults hospitalized for acute stroke, 1995-2008.